ChemInform Abstract: Photoinduced Decarbonylative Rearrangement of Bicyclo[2.2.2]octenones: Synthesis of the Marasmane Skeleton. Issue 11 (February 2016) - Wang, Chun‐Chieh; Ku, Yi‐Chen; Chuang, Gary Jing
Abstract: The fused‐5, 6, 3‐tricyclic ring structure of the marasmane sesquiterpenoid skeleton is formed via a photo‐induced decarbonylative 1, 3‐migration reaction of bicyclo[2.2.2]octenone derivatives such as (I), (III), and (V).